Northern Bobwhite Survival, Nest Success, and Habitat Use in Kentucky During the Breeding Season - Andrew S. West; Patrick D. Keyser; John J. Morgan (National Quail Symposium Proceedings, 2017)
Northern bobwhite (Colinus virginianus) populations have experienced protracted declines over much of their range. There has been an annual decrease of 2.61% since the 1960s in Kentucky, an area representative of the Mid-South where there is a lack of data on basic population parameters. Much of the decline is attributed to prevailing land-use practices and associated habitat loss. We monitored northern bobwhite on a 515-ha farm in Oldham County, Kentucky to assess survival rates, nest success rates, and habitat use in the Mid- South. The farm consisted of row crops, cool-season pastures and hay (primarily tall fescue), fallow native warm-season grass fields, and woods. We captured birds using baited funnel traps and fitted them with harness radio transmitters and monitored them daily during April–August, 2009 and 2010. We radiomarked 88 birds (40 females, 48 males) and monitored 24 nests, 9 (37.5%) of which were successful, over the 2 years. Survival rates were 25.3 and 27.9% for 2009 and 2010, respectively, based on estimates from Program MARK. Home range size (54.0, range 1⁄4 38.0–55.9 ha) did not differ by sex, age, or year (P .0.05). Quail favored food plots in both years and avoided developed areas.
Keywords: Colinus virginianus; habitat use; home range; Kentucky; nest success; northern bobwhite; radiotelemetry; survival rate